The Other Crisis - Wolfensohn, James D. (2017)
This is a speech given by James D. Wolfensohn, President of the World Bank Group, at the Annual Meetings held in Washington D.C., on October 6, 1998. It sets out the Bank's role and mission in dealing with the human crisis that has received so little attention in the media. Dealing with that crisis requires long-term work on both the social and the structural agendas. The speech also lays out a new "development framework." Such a framework would allow countries to look at the totality of change necessary to make development inclusive and sustainable.